Perancangan Dies dan Roller Pada Mesin Pellet biomassa - Darwin Sugandi (Journal of Mechanical Engineering, 2026)
The problem of fossil energy limitations encourages the development of renewable energy, one of which is biomass. Wood powder waste that has been underutilized has the potential to be processed into biomass pellets as an environmentally friendly alternative fuel. This study aims to design dies and rollers on biomass pellet machines that are capable of processing wood powder waste into cylindrical pellets with a focus on their strength and safety analysis. The methods used to determine strength and safety are simulations using solidworks as well as theoretical calculations to validate the results. The results showed that the design of dies with a hole diameter of 8 mm and a suitable roller can produce biomass pellets with a good level of density and efficiency. Simulations of voltage, strain and safety factors on components indicate a safe and feasible design to implement. This research contributes to the development of biomass pellet machine technology and the use of wood powder waste into renewable and environmentally friendly energy.